Embodying The Meaning Of The Guardian Of The Constitution In The Role Of The Constitutional Court Of Reducing Constitutions Indicated By Policy Corruption - Suharno, Suharno; Junaidi, Amir; Aziz Zaelani, Muhammad (CV. Inara, 2021)
Purpose of this study was to answer two problems: (i) how is the guardian of the constitution embodied through the function of the Constitutional Court; and (ii) how the Constitutional Court as the guardian of the constitution reduces constitutions that are indicated by the policy corruption. Policy corruption is an invisible and covert element that able to threaten the synergy of the legal system and the public interest. The form of policy corruption is realized in the form of a law. Efforts that can be made to reduce the policy corruption are to implement the tight control over the media, which in this case is relevant to the function of the Constitutional Court. This studywas classified as doctrinal research with primary and secondary legal materials. Comparative approach and case approach were used to answer the legal issues. The results showed that: First, the guardian of the constitution through the function of the Constitutional Court through the optimization of the Constitutional Court Judges as the agent of constitution, strengthening the execution of the Constitutional Court decisions and collaborative steps with other state institutions in enforcing the constitutional guardianship. Second, the Constitutional Court as the guardian of the constitution in reducing laws indicated by the policy corruption is manifested in the form of a Constitutional Court decision that can be retroactive to recover the impact of legal losses that are indicated by the policy corruption, the decision of Constitutional Courtis justified by ultra vires to anticipate the chain of constitutions that indications of policy corruption, the decision of Constitutional Courtis strengthened in terms of its execution and the Court can examine or test the Constitution Drafting (bill/ RUU) (a priori review) as a preventive measure to prevent the enactment of laws that indicate policy corruption.